Pedagogical Content Knowledge of Mathematics Teachers: A Focus on Identifying and Correcting Sources of Students’ Misconceptions in Linear Programming - Wakhata, Robert; Mutarutinya, Vedaste; Balimuttajjo, Sudi (The international journal of pedagogy and curriculum, 2022)
This study explored the pedagogical content knowledge (PCK) of mathematics teachers on the topic of linear programming (LP). Specifically, the study examined the teachers’ abilities and their judgment in using their PCK to identify the sources and causes of students’ difficulties in learning LP. First, 291 mathematics teachers participated in the survey. This was followed by an interventional study involving eight teachers, four from central Uganda and four from eastern Uganda. The eight teachers were asked to explain the ideal way to teach secondary school students the topic of LP. A descriptive qualitative survey research design for multiple case studies was adopted. A LP learning questionnaire, an interview protocol, and the classroom observation scale constituted data collection tools. The results showed the existence of substantial differences in the mathematics teachers’ PCK. The students’ challenges in LP mainly stemmed from four categories of PCK (subject matter knowledge, curriculum knowledge, student knowledge, and knowledge of teaching methods and strategies). To integrate these knowledge components, teachers emphasized the development of students’ conceptual and procedural knowledge with a variety of step-by-step activities designed to promote problem-solving and inquiry for students’ understanding of LP and related concepts. This research recommends the integration and application of numerous methods for identifying and effectively overcoming students’ learning challenges in LP to enhance teacher didactical practices. Routine in-service specialized training workshops may be adopted to bring together teachers to share their experiences on the best instructional practices for enhancing and promoting students’ proficiency in mathematics and LP in particular.